Perhitungan Biaya Produksi Menggunakan Metode Full Costing Dalam Penentuan Harga Jual Kayu Gergajian(Studi pada Industri Kayu di Kecamatan Danau Teluk Kota Jambi: Perhitungan Biaya Produksi Menggunakan Metode Full Costing Dalam Penentuan Harga Jual Kayu Gergajian(Studi pada Industri Kayu di Kecamatan Danau Teluk Kota Jambi - Saydatun Nisya1; Mohammad Orinaldi Mohammad Orinaldi (Journal of Islamic Accounting Competency, 2026)
This study investigates the use of the full cost method for calculating production costs in the wood industry located in Danau Teluk District, Jambi City. Utilizing qualitative research methods, data were gathered through observations, interviews, and documentation. The study focused on four wood industries: CV. Tri Tunggal Sawmill, CV. Meranti Jaya Makmur, CV. Conta Dora, and Maju Bersama Sawmill. Findings reveal that the wood industry in this district has not adopted production cost calculations that align with cost accounting standards. Specifically, two companies priced their products based on regional market prices, while the other two relied on gross and unstructured pricing methods. The full costing method analysis included all cost components: raw materials, direct labor, variable factory overhead, and fixed factory overhead. Production costs calculated for CV. Tri Tunggal Sawmill were Rp 282,172,000 for a production volume of 168 m³; CV. Meranti Jaya Makmur calculated costs of Rp 270,327,666 for the same volume. CV. Conta Dora's costs reached Rp 516,512,000 for a production volume of 336 m³, and Maju Bersama Sawmill reported costs of Rp 440,231,000 for 264 m³. Data were derived from production results reported in June 2025